Impact of Agricultural Productivity on Small Farmers' Financial Wellbeing: The Role of Microfinance - Utami, Novia; Sitanggang, Marsiana Luciana (Direktorat Riset dan Pengabdian kepada Masyarakat Universitas Bina Darma, 2024)
This study aims to explore the impact of agricultural productivity on farmers' financial wellbeing in Indonesia and the moderating role of microfinance in this relationship. The findings reveal that microfinance has a significant positive impact on farmers' financial wellbeing. Access to microfinance services allows farmers to obtain the necessary credit to invest in high-quality agricultural inputs, such as seeds, fertilizers, and modern equipment, which, in turn, enhances agricultural productivity and farmers' income. Additionally, increased agricultural productivity is significantly positively correlated with financial wellbeing. Higher productivity leads to greater crop yields and increased income from the sale of agricultural products. However, the study also finds that microfinance does not significantly moderate the relationship between agricultural productivity and financial wellbeing. This indicates that while microfinance contributes directly to financial wellbeing, it does not substantially enhance the effect of agricultural productivity on financial outcomes. Other factors, such as market access, infrastructure, and training, may play a more significant role in influencing this relationship.